THE WINEMAKING INDUSTRY IN THE SOCIETY OF JESUS’ PROPERTIES IN SANTIAGO OF CHILE. A BIBLIOGRAPHICAL REVISION. - Sottorf Neculhueque, Carlos (Revista de Historia Social y de las Mentalidades, 2015)
This article seeks to approximate way how  the Society of Jesus started to develop an  important economic power in Chile since the  late  XVI century, based especially on farming  properties and production, with especial  emphasis on wine production. The Society of  Jesus acquired properties, and some of them  reached important levels in terms of production  and administration, being wine production one  of the many branches in their enormous trading  web. It is important to highlight the importance  wine had for the Society of Jesus, since it  was used as a payment mean in agricultural  activities, such as the rodeo and harvests.  In this manner, the winemaking activity it  is portrayed as part of the diversification of  the productive units of the company, which  improved their harvest techniques and,  therefore, increased their productive rates  outstandingly.
Keywords: Society of Jesus; Wine; Vineyard-farming